Thermal effects of bioimplants. - Lazzi, G.
Implantable devices are well on the way to becoming small, dedicated, and highly complex embedded systems. As such, they are plagued by the same thermal management problems that afflict the computer industry: increased functionality causes increased heat generation. Herein, the effects of various parameters on the temperature increase in the human body tissue are considered, with a focus on a specific proposed implant: a dual-unit retinal prosthesis to restore partial vision to the blind . This particular example is educative since it includes most of the potential causes of thermal dissipation: a microchip that could dissipate relatively large power, a telemetry system, and a potentially large number of stimulating electrodes. The power dissipation characteristics of implanted electronic systems will have increasing importance for the design of future implantable devices. It was shown in this article that in some cases, this power dissipation can lead to temperature increases in the human tissue that are not negligible. In particular, the design of implantable stimulating devices with a large number of stimulating channels must be performed with a clear idea of the potential thermal implications of the device. Fortunately, reliable numerical and experimental methods are available to characterize the temperature increase caused by the implantable device. These methods should be used during the design phase of these devices.
Keywords: Bioimplants; Blind; Dual-unit retinal prosthesis; Heat generation; Human body tissue; Implantable devices; Implantable stimulating devices; Implanted electronic systems; Microchip; Partial vision restoration; Power dissipation; Stimulating electrodes; Telemetry system; Thermal dissipation; Thermal effects